The effect of sawdust on shear strength properties of peat soil - Nik Nor Hasliza , Bekhari (2013)
Peat is in the type of soft soil and consider as a problematic soil by engineers which should be avoided if possible. This is due to the low shear strength and high compressibility which are not suitable for construction. With rapidly growth of development infrastructures facilities in Malaysia, the price of lands are very expensive and very limited and, it may impossible to avoid any construction on the soft soil especially peat soil. Soil improvement needed to do to in order overcome this related problem. This paper presents the effects of rice husk on the shear strength of peat soil. The effects of rice husk by proportion have been investigated in this study. The properties and shear strength of peat soil taken from Kampung Tanah Puteh, Pekan, Pahang were determined by experimentally investigation. The direct shear test was performed to determine the parameters of shear strength which are cohesion and angle of shear resistance and also to determination the optimum mix of rice husk with peat soil mix which gives the maximum shear strength. The test was done on 18 samples with different mixed proportion of 0%, 0.5%, 1.0%, 1.5%, 2.0% and 2.5% of rice husk subjected to normal stress of 136.2kPa, 272.5kPa and 408.8kPa for each of the proportion. The study revealed that adding rice husk at exact value can give the maximum value of shear strength. The shear strength parameter which is cohesion is inversely proportional to the angle of shear resistance. The optimum mix was 1.5% rice husk with peat proportion.